Directional sound field decay analysis in performance spaces. Issue 3 (September 2021) - Berzborn, Marco; Vorländer, Michael
The analysis of the spatio-temporal features of sound fields is of great interest in the field of room acoustics, as they inevitably contribute to a listeners impression of the room. The perceived spaciousness is linked to lateral sound incidence during the early and late part of the impulse response which largely depends on the geometry of the room. In complex geometries, particularly in rooms with reverberation reservoirs or coupled spaces, the reverberation process might show distinct spatio-temporal characteristics. In the present study, we apply the analysis of directional energy decay curves based on the decomposition of the sound field into a plane wave basis, previously proposed for reverberation room characterization, to general purpose performance spaces. A simulation study of a concert hall and two churches is presented uncovering anisotropic sound field decays in two cases and highlighting implications for the resulting temporal evolution of the sound field diffuseness.